Problems and Solutions Concerning the Distance Protection of Transmission Lines Connected to Inverter-Based Resources - Juan David Hernández-Santafé; Elmer Sorrentino (Energies)
This article presents a review of the problems and solutions concerning the distance protection of transmission lines connected to inverter-based resources (IBRs). After a brief description of IBRs and distance protection, the reported problems are classified based on their causes and effects. The causes are related to IBR behavior, and the effects are related to distance protection. The effects are classified as overall effects (observable wrong trips or an observable lack of activation of distance functions) and specific effects (related to the particular internal relay elements that failed, causing the observable overall effects). Furthermore, special attention is paid to clearly describe the research literature from relay manufacturers, since it should be closer to the current trends related to real-life problems and solutions. The causes and specific effects particularly mentioned in the reviewed literature are summarized in corresponding tables, including information about those papers where such causes and effects cannot be clearly identified.